Harmonization of human life in the concept of jagad gedhe and jagad cilik of Javanese society - Nugroho, Yohanes Dwi; Riyanto, Armada (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2024)
This study investigates the symbolic meanings within the concepts of jagad gedhe and jagad cilik in Javanese society, emphasizing the harmonization of human relationships with others and the environment. A qualitative descriptive method based on literature studies was employed, utilizing Ernst Cassirer's philosophy of symbols. Data were collected through reading and note-taking, and their validity was ensured through source triangulation. The findings reveal that the concepts of jagad gedhe (macrocosm) and jagad cilik (microcosm) underscore the importance of balance among humans, their peers, and nature. By applying symbolic philosophy, these concepts provide practical solutions such as promoting positive cultural expressions, considering socio-ecological impacts, and fostering sustainable development. The study emphasizes that human life harmonization can be achieved by cultivating ethical awareness through cultural symbolic meanings. Practical implications include balanced human-nature relationships, promoting cultural values, and supporting sustainability as the foundation of ethical living.